Overcoming over-identification: The power of organizational prestige in optimizing sales performance. Issue 3 (18th March 2019) - Vieira, Valter Afonso; da Silva, Juliano Domingues; Gabler, Colin
Abstract : Purpose: The purpose of this paper is threefold: first, to determine the impact of interpersonal identification on sales performance; second, to uncover whether or not that relationship changes direction based on levels organizational prestige; and third, to test the antecedent of managerial support on salesperson interpersonal identification. Ultimately, the authors want to provide sales managers with tangible ways to nurture the self-concept of their sales force while optimizing sales performance. Design/methodology/approach: The authors test the hypotheses using a data set of 196 B2C retail salespeople in the shoe industry. Respondents answered a printed questionnaire, which was analyzed using multiple linear regression and response surface analysis. Findings: The authors find that managerial support does positively influence interpersonal identification among salespeople which, in turn, increases sales performance. However, the relationship is curvilinear, becoming negative when over-identification occurs. This inverted U-shaped relationship is moderated by organizational prestige such that the negative influence is overcome by employees who have pride and confidence in their organization. Practical implications: Managers should balance the level of support that they provide their employees. While this mentorship generally leads to positive results, too much can lead to over-identification, and consequently reduce sales performance. However, this negative effect can be overcome if the salesperson perceives his organization as prestigious. Therefore, a mix of guidance and autonomy may foster the strongest self-concept among the sales team and generate the most positive outcomes. Further, managers should monitor their employees' perceptions of the company, communicating its strong reputation internally to generate organizational prestige. Originality/value: The authors extend social identity theory in a sales context to provide a better understanding of how self-concept can be altered – for better or worse – by the sales manager. The authors also show the importance of communicating your company's social value to employees. While over-identification in the manager–employee dyad can create a "tipping point" where sales performance begins to decrease, organizational prestige may be able to overcome this effect, demonstrating the power of prestige. Together, the authors present the importance of contextual and external influences on individual sales performance.